MicroRNA‐7 inhibition rescues age‐associated loss of epidermal growth factor receptor and hyaluronan‐dependent differentiation in fibroblasts. Issue 2 (12th November 2013) - Midgley, Adam C.; Bowen, Timothy; Phillips, Aled O.; Steadman, Robert
Summary Age‐related defects in fibroblast differentiation were previously shown to be associated with impaired hyaluronan synthase 2 (HAS2) and epidermal growth factor receptor (EGFR) function, with both required for normal fibroblast functionality. In fibroblasts, transforming growth factor‐beta 1 (TGF‐β1)‐dependent phenotypic activation uses two distinct but co‐operating pathways that involve TGF‐β receptor (TGF‐βR)/Smad2 activation and HA‐mediated CD44‐EGFR co‐localization and signalling through extracellular signal‐regulated kinase 1/2 (ERK1/2). The HA‐mediated CD44‐EGFR pathway was found to be compromised with in vitro aging, through loss of EGFR expression and a reduced movement of CD44 throughout the cellular membrane. Here, we also investigate the involvement of microRNAs (miRNAs) in age‐related loss of differentiation, through investigation of miRNA‐7 (miR‐7) regulation of the HA‐mediated EGFR‐signalling pathway. The transcription of miR‐7 was found to be upregulated in aged cells. In young cells, age‐related loss of differentiation could be mimicked through transfection of pre‐miR‐7, and in aged cells, could be reversed through transfection of locked nucleic acids (LNA) targeting miR‐7. Additionally, miR‐7 was found to be involved in the regulation of CD44 membrane motility, which was downregulated in instances of miR‐7 upregulation, and partially restorable through either miR‐7 inhibition or HAS2 overexpression. The altered dynamics of CD44 in the cell membrane demonstrated a further action of miR‐7 in regulating the HA‐dependent CD44/EGFR pathway. We explain this novel mechanism of age‐associated functional consequence due to miR‐7 upregulation and demonstrate that it is reversible; highlighting miR‐7 as a potential target for restoring the healing capabilities in chronic wounds in the elderly.